Development of Augmented Reality-Based Interactive “Element Card” Media on Electron Configuration Submaterial According to Niels Bohr - Mariatul Qibtiyah; Sukarmin Sukarmin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to obtain the feasibility of Augmented Reality-based Element Card interactive media on the electron configuration submaterial according to Bohr's theory. This research uses a 4D model which is only carried out until the development stage. This research was conducted at SMAN 1 Gedangan Sidoarjo on 30 students X IPA. This study used a validation sheet instrument, pretest and posttest questions, student response questionnaires, and student observation questionnaires. If the value of the validation result is ≥ 61% then it is considered valid, the practicality value is ≥ 61% then it is considered practical, and the effectiveness value if it is classified above 0.3 which includes medium or high then it is considered effective. The results of content and construct validation are 88% and 84% are included in the very valid category. Practicality was obtained from 94.86% and 97% of student responses and observations included in the very practical. The effectiveness is obtained from learning outcomes by calculating the N-Gain and Wilcoxon Signed Ranks Test, the value of Asymp. Sig (2 tailed) is 0.000 which is smaller than 0.05 so there is a difference in the students' pretest and posttest scores. This proves that the interactive media based on the Augmented Reality Element Card can be used for chemistry learning media.